2011
DOI: 10.3389/fpsyg.2011.00153
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Concentrative Meditation Training on the Development of Attention Networks during Early Adolescence

Abstract: We investigate if concentrative meditation training (CMT) offered during adolescent development benefits subsystems of attention using a quasi-experimental design. Attentional alerting, orienting, and conflict monitoring were examined using the Attention Network Test (ANT) in 13–15 year old children who received CMT as part of their school curriculum (CMT group: N = 79) vs. those who received no such training (control group: N = 76). Alerting and conflict monitoring, but not orienting, differed between the CMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 64 publications
4
47
1
Order By: Relevance
“…Schonert-Reichl and Lawlor (2010) speculated that developmental changes between preadolescents and early adolescents might account for the different effects of meditation upon general self-concept after meditation. Baijal et al (2011) also found age-related effects of meditation upon conflict monitoring. Warner's (2005) study was sensitive to developmental effects and used two different variants of TM with two different age groups: TM was used with students over the age of 10, while Words of Wisdom was used with students who were aged 10 or younger.…”
Section: Methodological Considerations and Future Researchmentioning
confidence: 76%
See 2 more Smart Citations
“…Schonert-Reichl and Lawlor (2010) speculated that developmental changes between preadolescents and early adolescents might account for the different effects of meditation upon general self-concept after meditation. Baijal et al (2011) also found age-related effects of meditation upon conflict monitoring. Warner's (2005) study was sensitive to developmental effects and used two different variants of TM with two different age groups: TM was used with students over the age of 10, while Words of Wisdom was used with students who were aged 10 or younger.…”
Section: Methodological Considerations and Future Researchmentioning
confidence: 76%
“…Hence, an educated guess from the adult neuroscience research must be made to suggest that meditation can change the brain of students in ways that increase cognitive function and emotional regulation. This educated guess is supported by the evidence that school-based meditation programmes have found outcomes showing improved cognitive function and emotional regulation (Baijal et al 2011;Schonert-Reichl and Lawlor 2010). Detailed evidence from the three strands of research that have been integrated to build the School-Based Meditation Model will be presented below.…”
Section: Why Does Meditation Influence Student Outcomes?mentioning
confidence: 98%
See 1 more Smart Citation
“…We know of no papers assessing the possibility of developmental change in conflict adaptation effects during this period. However, several papers chart the development of conflict adaptation effects in childhood and adolescence (e.g., Baijal et al, 2011;Kray et al, 2012) and the decline of conflict adaptation with aging (e.g., Monti Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are in particular measured by the Attentional Network Test (ANT) (Fan et al 2002) and its modifications (see Di Francesco et al 2017), with some differential findings based on duration and type of meditation practice (e.g., Baijal et al 2011;Jha et al 2007;Tang et al 2007;van den Hurk et al 2009). Sustained attention tasks have also been used for cognitive performance assessment associated to mindfulness training (Jha et al 2017;Lutz et al 2009).…”
Section: Introductionmentioning
confidence: 99%